2002
DOI: 10.1002/gcc.10056
|View full text |Cite
|
Sign up to set email alerts
|

Heterogenic molecular basis for loss of ABL1‐BCR transcription: Deletions in der(9)t(9;22) and variants of standard t(9;22) in BCR‐ABL1‐positive chronic myeloid leukemia

Abstract: The objective of this study was to characterize the ABL1-BCR fusion gene in 76 BCR-ABL1-positive chronic myeloid leukemia (CML) patients regarding expression as well as genomic status, to assess the frequency of ABL1-BCR gene deletion in these patients, which has been reported to be an adverse prognostic factor in Philadelphia chromosome-positive CML. Patients were analyzed for ABL1-BCR 1b-b3 and/or 1b-b4 transcription by RT-PCR analysis. ABL1-BCR gene status was analyzed by FISH in 16 CML patients with no ABL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 22 publications
3
22
0
Order By: Relevance
“…All patients who lacked an intact ABL/BCR signal, either via deletion or physical disruption of the loci, also lacked detectable expression of the fusion gene as demonstrated previously by ourselves and others (de la Fuente et al, 2001;Huntly et al, 2002;Loncarevic et al, 2002). In contrast, of three patients with fusion of 5¢ABL and 3¢BCR FISH signals tested by RT-PCR, only two were shown to express an ABL-BCR transcript, while in the remaining patient no expression was detected.…”
Section: Abl-bcr Analysissupporting
confidence: 75%
See 3 more Smart Citations
“…All patients who lacked an intact ABL/BCR signal, either via deletion or physical disruption of the loci, also lacked detectable expression of the fusion gene as demonstrated previously by ourselves and others (de la Fuente et al, 2001;Huntly et al, 2002;Loncarevic et al, 2002). In contrast, of three patients with fusion of 5¢ABL and 3¢BCR FISH signals tested by RT-PCR, only two were shown to express an ABL-BCR transcript, while in the remaining patient no expression was detected.…”
Section: Abl-bcr Analysissupporting
confidence: 75%
“…One such patient was recently reported by Loncarevic et al (2002). The authors speculated that the variant Ph rearrangement in this patient had occurred via two serial translocations, as four breaks must be necessary to maintain the integrity of ABL-BCR.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…by guest www.bloodjournal.org From no impact on the prognosis of CML. 29 Further, some studies have suggested that patients with variant translocations do have adverse outcomes, 4,[30][31][32][33] whereas others have reported that such translocations have no influence on response or survival. 6,8,[34][35][36][37] A previous analysis reported 44 cases with variant translocations in a series of 721 patients (4%) who had failed prior interferon therapy and were either in CP or the accelerated phase.…”
Section: Discussionmentioning
confidence: 99%